Why do users stay? Emotional vs. functional attachment in pan-entertainment live streaming platforms - Zhang, Shu; Ji, Tie; Liang, Kai; Wei, Le; Pan, Younghwan (Frontiers in Psychology, 2025)
This study aims to investigate how emotional and functional attachments influence users’ continuance intention on pan-entertainment platforms. With pan-entertainment live-streaming booming, clarifying the psychological forces that keep users loyal is crucial. Prior studies rarely examined how emotional and functional bonds act together. Grounded in the Cognitive-Affective-Behavioral Intention (CABI) framework and attachment theory, this study tests a dual-path model on 306 valid responses, the findings reveal that attraction, perceived enjoyment, interactivity, and entertainment significantly enhance emotional attachment, whereas attraction and interactivity also positively influence functional attachment. Notably, perceived enjoyment and entertainment do not significantly impact functional attachment, suggesting that functional reliance is driven more by instrumental utility than hedonic value. Both emotional and functional attachments are found to be strong predictors of continuance intention. This study advances the CABI framework by incorporating dual-path attachment mechanisms, providing novel insights into user-platform relationships in live streaming contexts. Practically, the findings highlight the importance of real-time interaction features and personalized content recommendations in fostering emotional engagement and strengthening user retention.